2019
DOI: 10.1007/s11356-019-05533-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecologically relevant concentrations of Boral® 500 SC, Glifosato® Biocarb, and a blend of both herbicides on markers of metabolism, stress, and nutritional condition factors in bullfrog tadpoles

Abstract: The aim of this study was to verify the effects of the isolated forms of Boral® SC 500, Glifosato® Biocarb herbicides, and a blend of both herbicides on metabolism and oxidative balance markers of Rana catesbeiana tadpoles and on their nutritional condition. Groups of tadpoles were divided into different treatments: control (no herbicides), Boral® 500 SC (sulfentrazone: 130 μg/L), Glifosato® Biocarb (glyphosate: 234 μg/L), and a blend of both herbicides. After 7 days, the liver, caudal muscle, and blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Hyperstimulation of the nervous system causes energy demands, which activate hormone-sensitive triglyceride lipase in tissue, resulting in hydrolysis of stored triglycerides from fat stores and mobilization of free fatty acids in the bloodstream, resulting in increased serum total lipid concentration (Pothu et al 2019 ). These results agreed with those of Wilkens et al ( 2019 ) who found an increase in TG and very low-density lipoprotein (VLDL) levels in the plasma of bullfrog tadpoles exposed to two herbicides (sulfentrazone and glyphosate).…”
Section: Discussionsupporting
confidence: 93%
“…Hyperstimulation of the nervous system causes energy demands, which activate hormone-sensitive triglyceride lipase in tissue, resulting in hydrolysis of stored triglycerides from fat stores and mobilization of free fatty acids in the bloodstream, resulting in increased serum total lipid concentration (Pothu et al 2019 ). These results agreed with those of Wilkens et al ( 2019 ) who found an increase in TG and very low-density lipoprotein (VLDL) levels in the plasma of bullfrog tadpoles exposed to two herbicides (sulfentrazone and glyphosate).…”
Section: Discussionsupporting
confidence: 93%
“…Glyphosate has a high solubility in the aquatic environment and binds to soil particles and solid surfaces, which increases its availability and accumulation. Especially due to improper application practices, the widespread presence of glyphosate has been observed in the aquatic environment and surface water (Peruzzo et al 2008; Osten and Dzul‐Caamal 2017; Berman et al 2018; Wilkens et al 2019). In the reviewed files, we observed that the aquatic species most studied for the effect of glyphosate were R. quelen , Poecilia reticulata , and D. rerio .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no mortality has been observed in experiments using tadpoles exposed to ecologically relevant concentrations of several herbicides (Dornelles and Oliveira, 2014;Wilkens et al, 2019).…”
Section: Discussionmentioning
confidence: 99%